Optimalisasi Overload Traffic Dan Request Cloud Environment Menggunakan Metode Content Delivery Network Dan Private Zone Di RCTI+ - Satria Yana Putra; Irwan Agus Sobari (FORMAT, 2023)
Since 2019 Indonesia has had rapid development, especially in the digital industry, recorded at the 2020 World Economic Forum. Indonesia has 2,193 startup companies engaged in the digital field. It can also affect the ability of these companies to address existing or future digital problems. As is known, down or system failure in a server can cause losses in the company's economy. For a company the size of Facebook alone, it could suffer a loss of 99.75 million US Dollars. One of the causes of server failure is Overload Traffic and Request Cloud Environment caused by the large number of requests submitted to the server. Requests submitted to the server are recorded into 2 data, namely, CCU (Count Current User) and Traffic. In this study, the author uses the CDN and Private zone methods on Alibaba Cloud to share the server load so that there is no downtime or server failure caused by Overload Traffic and Request Cloud. It is hoped that this research can be helpful to networking engineers in overcoming Traffic Overload and Request Cloud, especially on Alibaba Cloud.